PELATIHAN MEMBUAT POSTER MENGGUNAKAN CANVA UNTUK MENAMBAH PENGETAHUAN DESAIN GRAFIS SISWA KELAS X SMK CENDEKIA BATUJAJAR - Ernawati, Tati; Syams, Fawwaz Muhammad; Sugianto, Castaka Agus; Rohmayani, Dini; Ekawati, Nia; Tresnawati, Shandy (ASOSIASI IDEBAHASA KEPRI, 2025)
The development of information technology in graphic design has opened many opportunities for vocational high school students to acquire skills that will be used in the workplace. This program aims to provide comprehensive training covering theoretical and practical aspects of product poster design using the Canva application for class X office automation and management students at SMK Cendekia Batujajar. The training method combines face-to-face learning, technical demonstrations, and hands-on practicum sessions. The activity was conducted on May 7, 2025, involving 37 students (4 male, 33 female) in the school's computer laboratory. The training materials covered product poster concepts, design functions in business, basic graphic design principles and introduction to Canva usage. Evaluation was conducted through online quizzes using Kahoot.it and practical design assignments. The results showed high participant enthusiasm evidenced by active discussions with instructors and utilization of break time for additional practicum. The school provided positive feedback and expressed hope for similar activities in the future. This training successfully enhanced students' graphic design competencies and provided new knowledge about design concepts and principles in poster creation.